2.
[tex]\frac{196^{2}}{14^{2}} = (\frac{196}{14})^{2} = 14^{2}=196\\\\(-2,5)^{3}:0,5^{3} = (-2,5:0,5)^{3} = (-25:5)^{3} = (-5)^{3}=-25\\\\(-1\frac{1}{3})^{4}:(\frac{2}{3})^{4} = (-\frac{4}{3})^{4}:(\frac{2}{3})^{4} = (-\frac{4}{3}:\frac{2}{3})^{4} =(-\frac{4}{3}\cdot\frac{3}{2})^{4} = (-2)^{4} = 16[/tex]
3.
[tex]a) \ (-8)^{2}\cdot(-2\frac{1}{3})^{2}\cdot(-\frac{3}{7})^{2} =(-8\cdot(-\frac{7}{3})\cdot(-\frac{3}{7}))^{2} = (-8\cdot1)^{2} = (-8)^{2} =64[/tex]
[tex]b) \ (7,2)^{3}\cdot(-\frac{5}{18})^{3}:(-0,8)^{3} = (7,2:(-0,8)\cdot(-\frac{5}{18}))^{3} = (-9\cdot(-\frac{5}{18}))^{3} =(\frac{5}{2})^{3} =\\\\= \frac{125}{8}=15\frac{5}{8} = 15,625[/tex]